Autoethnographic Reading of Jamling Tenzing Norgay’s Touching my father’s soul - Upadhayay, Toya Nath; Sharma, Prakash (Dhaulagiri Journal of Contemporary Issues, 2025)
Summitting the high peaks for looking around has historically been one of the most eminent desires of human beings. However, until a couple of centuries ago, mountaineering expeditions were rare due to multiple reasons such as divine cause, fear of danger, and lack of proper technologies, skills and knowledge. After European colonization began and expanded, the Europeans’ mountaineering fantasy also intensified significantly. Climbing became a testing mark for their bravery, adventure and perseverance. In the context of Nepal, after mountaineering was opened to visitors in the 1950s, there has been a mushrooming growth of climbers on different eight-thousanders including Everest. Consequently, each year, detrimental results like commodification of mountains, environmental degradation, cultural impacts, and untimely deaths have escalated. In the climbing season of 1996 only, twelve climbers lost their lives, which has widely drawn the media’s attention. Till date, more than seventeen books about have been produced about it. Jamling Tenzing Norgay is the only Nepali writer to write about this event from an insider’s perspective. This paper reads his Touching my father’s soul to explore autoethnographic elements. Based on qualitative research design, the paper analyzes and interprets the primary text by engaging relevant critical responses and the concept of autoethnography. Finally, the paper concludes that Jamling’s narrative offers his serious concerns about the socio-cultural and economic impacts of mountain tourism in addition to his personal stories. The study will contribute to the understanding of Jamling, Sherpa lifestyle and Sherpas’ connection to mountain tourism.